Ocean Acidification Impairs Foraging Behavior by Interfering With Olfactory Neural Signal Transduction in Black Sea Bream, Acanthopagrus schlegelii - Jiahuan, Rong; Wenhao, Su; Xiaofan, Guan; Wei, Shi; Shanjie, Zha; Maolong, He; Haifeng, Wang; Guangxu, Liu (Frontiers in Physiology, 2018)
In recent years, ocean acidification caused by oceanic absorption of anthropogenic carbon dioxide (CO2) has drawn worldwide concern over its physiological and ecological effects on marine organisms. However, the behavioral impacts of ocean acidification and especially the underlying physiological mechanisms causing these impacts are still poorly understood in marine species. Therefore, in the present study, the effects of elevated pCO2 on foraging behavior, in vivo contents of two important neurotransmitters, and the expression of genes encoding key modulatory enzymes from the olfactory transduction pathway were investigated in the larval black sea bream. The results showed that larval sea breams (length of 4.71 ± 0.45 cm) reared in pCO2 acidified seawater (pH at 7.8 and 7.4) for 15 days tend to stall longer at their acclimated zone and swim with a significant slower velocity in a more zigzag manner towards food source, therefore taking twice the amount of time than control (pH at 8.1) to reach the food source. These findings indicate that the foraging behavior of the sea bream was significantly impaired by ocean acidification. In addition, compared to a control, significant reductions in the in vivo contents of γ-aminobutyric acid (GABA) and Acetylcholine (ACh) were detected in ocean acidification-treated sea breams. Furthermore, in the acidified experiment groups, the expression of genes encoding positive regulators, the olfaction-specific G protein (Golf) and the G-protein signaling 2 (RGS2) and negative regulators, the G protein-coupled receptor kinase (GRK) and arrestin in the olfactory transduction pathway were found to be significantly suppressed and up-regulated, respectively. Changes in neurotransmitter content and expression of olfactory transduction related genes indicate a significant disruptive effect caused by ocean acidification on olfactory neural signal transduction, which might reveal the underlying cause of the hampered foraging behavior.